2014
DOI: 10.17795/jhealthscope-17528
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Xylene From Air by Natural Iranian Zeolite

Abstract: Background: Aromatic organic solvents are extensively used in various industries. Xylene is a colorless, transparent liquid, with the characteristic odor of the aromatic hydrocarbons family, which is widely used in industries. Adsorption is a conventional method of purifying polluted air containing volatile organic compounds (VOCs). Zeolite has many unique properties such as high capacity, molecular sieve characteristics, nonflammability, thermal stability, and strong acid sites. Moreover, it is reconstructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…They reported that the adsorption decreases with increasing temperature and ∆H°is a negative value, which complies with the result of this study (39). Vhdat Parast et al found that by increasing the temperature, xylene adsorption on clinoptilolite is declined (40).…”
Section: Discussionsupporting
confidence: 92%
“…They reported that the adsorption decreases with increasing temperature and ∆H°is a negative value, which complies with the result of this study (39). Vhdat Parast et al found that by increasing the temperature, xylene adsorption on clinoptilolite is declined (40).…”
Section: Discussionsupporting
confidence: 92%
“…Asilian also reported that increasing the amount of adsorbent cause to increase the adsorption efficiency. In fact, in this study, adsorption efficiency in low flowrate is was excellent and consistent [24]. Lu et al showed that the carbon nanotube oxidized with sodium hypochlorite had a higher BTEX adsorption than carbon nanotube and granular activated carbon.…”
Section: Discussionsupporting
confidence: 79%
“…The results of flow rate and amount of adsorbent in the present study were similar to the results of Asilian et al Asilian et al showed that the absorption capacity of xylene for zeolite was decreased up to 1.69 mg g -1 by increasing flow rate. Also, in a high flow rate, the time of failure and saturation time decreased in zeolite adsorbent [24]. Asilian also reported that increasing the amount of adsorbent cause to increase the adsorption efficiency.…”
Section: Discussionmentioning
confidence: 85%
“…The different features for VOCs' removal such as recovery (%), absorption capacity (AC), and aromatic compounds are compared together. Based on the results, the ST/HS-SPE procedure was comparable to other sorbent which was reported in different works (Bagheri Hosseinabadi et al 2019;Osanloo and Qurban-Dadras 2014;Faghihi Zarandi et al 2018;Jahangiri et al 2011;Hansmeier, 2010;Bina et al 2012;Shariq Vohra 2015;Qi et al 2018;Gholami et al 2014;Liu et al 2016;Rostami and Jonidi Jafari 2014;Vahdat Parast et al 2014;Britt et al Table 1 Validation…”
Section: Discussion and Comparing To Other Methodssupporting
confidence: 73%